Effect of infill pattern on mechanical properties of 3D printed PLA-Zn composites for drone frame structures: A topology optimization integrated application study - P. Arunkumar; D. Balaji; N. Radhika; L. Rajeshkumar; Sanjay Mavinkere Rangappa; Suchart Siengchin (Results in Engineering)
Material requirements and design optimization are two parallel verticals for the ever-growing material-based demands. The demand for enhanced properties of the materials can be satisfied by developing composite materials. The capability of additive manufacturing (AM) to handle complex geometries with ease has opened many avenues in topological optimization and lightweight structural design. In the current work, the drone frame has been modeled using Fusion 360 software and topological optimization was carried out to obtain a structural design with maximum load-carrying capacity with minimum material. Subsequently, PLA-Zn filament (with an 80:20 ratio) was used to develop composite specimens through the fused deposition modeling (FDM) 3D printing technique. The effect of various infill patterns on the 3D printed PLA-Zn specimens on the mechanical properties such as tensile, compressive, and impact strength and hardness were evaluated. All the tests were carried out as per ASTM standards. The results showed that the infill patterns such as octet and cubic exhibited higher mechanical properties with 0.56 kN tensile strength, 60.58 MPa compressive strength, 4.84 J/cm2 impact strength, and 80 shore D hardness. Subsequently, the drone frame was printed using the topologically optimized model with the infill pattern which exhibited maximum mechanical properties. The drone frame was also tested in real time for its mechanical strength. The topologically optimized 3D-printed drone frame with a cubic infill pattern can be used as a low-cost replacement for the currently used conventional frame.